Patients With Short Bowel on Narcotics During 2 Randomized Trials Have Abdominal Complaints Independent of Teduglutide. (9th August 2016) - Fujioka, Ken; Jeejeebhoy, Khursheed; Pape, Ulrich‐Frank; Li, Benjamin; Youssef, Nader N.; Schneider, Stéphane M.
Abstract : Background: Narcotic agents are frequently administered to manage increased intestinal motility in patients with short bowel syndrome, but long‐term use is associated with gastrointestinal (GI) complaints. This analysis evaluated the incidence of narcotic use and abdominal adverse events among patients with short bowel syndrome receiving teduglutide. Materials and Methods: Pooled data from patients who received ≥1 dose of teduglutide 0.05 mg/kg/d (n = 77) or placebo (n = 59) in either of 2 randomized, double‐blind, phase III studies were analyzed. Results: Of 136 patients, 52 (38%) received narcotics. GI adverse events occurred more often among patients who received narcotics than among those who did not (abdominal pain, 51% vs 21%; nausea, 42% vs 11%; abdominal distension, 17% vs 8%; vomiting, 19% vs 6%). Logistic regression analysis indicated that the probability of GI adverse events was significantly increased in patients with narcotic use ( P = .0009). In contrast, teduglutide treatment, as well as the interaction between teduglutide and narcotic use, did not affect the probability of GI adverse events. Conclusions: These results suggest that patients with short bowel syndrome receiving narcotics have chronic GI complaints independent of teduglutide treatment. Data included in this analysis were derived from ClinicalTrials.gov NCT00081458 and NCT00798967 (EudraCT 2004‐000438‐35 and 2008‐006193‐15).